Source of Byung-Chul Han's Philosophy of Time Theory - Yang, Meiting (Journal of Social Science and Humanities, 2024)
The concept of benign time is proposed by Byung-Chul Han in response to the diagnosis and criticism of time under the domination of digital capital, which is beneficial for human survival. It is based on Marx's view of time as the theoretical foundation of benign time. But this kind of fragrant and benign time does not come out of thin air. It is based on the previous interpretation of time and the diagnosis and criticism of real time. Marcel Proust's discourse on recalling time in his book In Search of Lost Time, Heidegger's interpretation of round-trip time, and Chinese incense's criticism and correction of the negative time in today's society dominated by digital capital provide different ideas and perspectives for his study of time philosophy.